Strange encounters: embodied others in post-coloniality - Ahmed, Sara (Routledge, 2000)
"Examining the relationship between strangers, embodiment and community, Strange Encounters challenges the assumptions that the stranger is simply anybody we do not recognize and instead proposes that he or she is socially constructed as somebody we already know. Using feminist and postcolonial theory this book examines the impact of multiculturalism and globalization on embodiment and community whilst considering the ethical and political implication of its critique for post-colonial feminism. A diverse range of texts are analyzed which produce the figure of 'the stranger', showing that it has alternatively been expelled as the origin of danger - such as in neighbourhood watch, or celebrated as the origin of difference - as in multiculturalism. The author argues that both of these standpoints are problematic as they involve 'stranger fetishism'; they assume that the stranger 'has a life of its own'". – Site de l'éditeur.
Keywords: approches et analyses; corps; cours; discipline; féminisme décolonial; histoire et politique; lit4700; philosophie; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; études culturelles

The cultural politics of emotion - Ahmed, Sara (Edinburgh University Press, 2014)
This is a bold take on the crucial role of emotion in politics. Emotions work to define who we are as well as shape what we do and this is no more powerfully at play than in the world of politics. Ahmed considers how emotions keep us invested in relationships of power, and also shows how this use of emotion could be crucial to feminist and queer political movements. Debates on international terrorism, asylum and migration, as well as reconciliation and reparation are explored through topical case studies. In this textbook the difficult issues are confronted head on. New for this edition: a substantial 15,000-word Afterword on 'Emotions and Their Objects' which provides an original contribution to the burgeoning field of affect studies; a revised Bibliography; and updated throughout.
Keywords: approches et analyses; capitalisme; corps; discipline; féminisme; histoire et politique; militance; philosophie; queer; ressource en ligne; sciences humaines; systèmes d'oppressions; thématiques; émotions; études culturelles